TELAAH KRITIS TERHADAP PERSPEKTIF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE DALAM LAPORAN KEUANGAN PEMERINTAH PUSAT REPUBLIK INDONESIA - Wahyu Rangga Saputra; Endang Kiswara (Diponegoro Journal of Accounting, 2025)
This study analyzed the correlation between Environmental, Social, and Governance (ESG) disclosure, Audit Quality, ROE, Leverage, Firm Size and the Public Value of the Indonesian Central Government. Utilizing secondary data from the Central Government Financial Statements (LKPP) and Audit Board (BPK) findings (2021-2023) through qualitative descriptive content and correlation analyses, findings revealed a very weak positive correlation for overall ESG with Public Value. Specifically, Environmental showed a weak positive, Governance a very strong positive, and Social a very strong negative correlation. These results suggest that despite the government possessing various ESG-related data, its lack of integration into a comprehensive reporting framework limits its optimal impact on government legitimacy and Public Value.